Blue growth - drivers and alternative scenarios for the Gulf of Finland and the Archipelago sea. Qualitative analysis based on expert opinions - Riitta Pöntynen; Anne Erkkilä-Välimäki (Turun yliopiston Brahea-keskus, 2022)
The scenario-building process was part of the Plan4Blue project, in a work package called “Potential for Sustainable Blue Economies”. The approach consists of multiple alternative future visions. The Plan4Blue scenario process produced both qualitative and quantitative data. Expert views were included in the process from the Delphi studies, the Helsinki and Tallinn scenario workshops, as well as from expert interviews. This report describes the methods and results of the expert involvement in the scenario process, main drivers and the alternative Blue Growth scenarios for the Gulf of Finland and the Archipelago Sea. Economic and socioeconomic analyses as well as the mapping process have been reported in other publications of the Plan4Blue project.